Handbook of Petroleum Refining Processes, Fourth Edition - Meyers, Robert A. (McGraw-Hill Education, 2016)
This fully revised resource presents the latest technologies and processes for petroleum refining from the world's leading producers, including Chevron, Shell, ExxonMobil, and UOP.